Neutralizing antibodies against IFN beta in patients with multiple sclerosis: a comparative study of two cytopathic effect tests (CPE) for their detection - Oliver-Martos, Begoña; Orpez, Teresa; Mayorga Mayorga, Cristobalina; Leyva-Fernández, Laura; López-Gómez, Carlos; Marín, Carmen; Luque, Gloria; Fernández Fernández, Óscar (Elsevier, 2009)
The purpose of this study is to monitor the development of anti-natalizumab antibodies to evaluate their first appearance in multiple sclerosis patients, since their presence has been associated with a reduction in the efficacy of the treatment and an increase of adverse events. A total of 134 multiple sclerosis patients were included in the trial. Anti-natalizumab antibodies were monthly detected by ELISA up to the first year of treatment and subsequently, a determination was made at 18 months. 15.7 % of the patients were positive, being 7.5 % transiently positive and 8.2 % persistently positive. The first appearance of anti-natalizumab antibodies occurred after the first month of treatment onset in 72 % of positive patients; 18 % did so after the second month, and 9.7 % after the third month. Antibodies were never detected for the first time after the fourth infusion. The development of anti-natalizumab antibodies occurs very early after treatment onset. This observation should be considered when standardizing the follow up of patients treated with this drug in order to minimize the risks and optimize the treatment.
Keywords: Esclerosis múltiple; Interferon beta treatment; Cytopathic effect method (CPE); Neutralizing antibodies (NABs); A549/EMCV; HEP2/VSV